GAP ANALYSIS OF STUDENTS’ EXPERIENCE AND EXPECTATIONS WITH SPECIAL REFERENCE TO MBA EDUCATION IN INDIA - Shetty, Bhavna R (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Understanding students’ viewpoints on teaching effectiveness within an academic system is one of the most important pre-requisite for creating a great learning organization. Teaching is a complex activity that should be measured on multiple dimensions using a combination of measuring techniques. The present study assumes that students are the best brand ambassadors of any management institute. The primary objective was to gain a deeper understanding of the relationships and the gaps between expectations of students entering MBA, their experiences at the end of first year and their teachers’ perceptions. The data were collected from MBA students and teachers in Nasik city. The results suggest that though faculty perceived to have delivered their best it did not reach students in same perspective. There was significant gap between students’ expectations and experiences and also between teachers’ perception and students’ experiences for all areas of teaching effectiveness. To reduce the gap, teachers need to be flexible in terms of incorporating students’ expectations and feedback into teaching learning process.